Vocational training for women empowerment: Saint Kuriakose Elias Chavara’s vision - Suja, V J; Mathai, Sebastian; Prakasha, G S (Intelektual Pustaka Media Utama, 2025)
The present study attempted to describe the initiatives of Saint (St.) Kuriakose Elias Chavara on vocational training and women’s empowerment. The study narrated the present condition of one of his vocational training initiatives known as “rosary-making,” which is in vogue at Koonammavu Village in Kerala state, India. The study employed a multi-method research design approach to carry out the present study. It included historical, qualitative, and quantitative methods in sequence. In the historical method, the study employed document analysis of primary and secondary sources. As a part of the qualitative method, the study conducted a semi-structured interview with 10 rosary-making entrepreneurs in Koonammavu. As a part of the quantitative method, the study administered a questionnaire to 100 families who are actively involved in the rosary-making business. Document analysis revealed that St. Chavara’s initiative on rosary-making vocational training for nuns was a contribution to women’s empowerment. Narrative thematic analysis revealed 5 main themes and 10 subthemes in Chavara’s contribution. Quantitative data revealed that rosary-making emerged as a livelihood, business, and source of income for many families. The study recommends future researchers focus on all the initiatives of St. Chavara in the realm of vocational training and women’s empowerment.